EVALUASI PELAKSANAAN WARUNG KAMTIBMAS DI KABUPATEN INDRAMAYU DI TAHUN 2014 - Donny Prasetyo; Reni Windiani; Lusia Astrika (Journal of Politic and Government Studies, 2016)
ABSTRACTION Warung Kamtibmas in response to the limited number of police personnel is considered to be solving the right problem, related to security and public order. But in reality the expectations of the formation Kamtibmas point different from the reality. Warung kamtibmas not working properly. Many cases Kamtibmas disorder that has been completed, but the results of the solution are not optimal and is not finished, giving rise to new problems again, like the case of brawl happened several times. Based on these problems it is necessary to evaluate the implementation of the program point Kamtibmas in Indramayu Police. The purpose of this research was to determine the implementation of the internal security point, the factors that affect the implementation of Warung Kamtibmas, and evaluation of the stalls kamtibmas in Indramayu in 2014. This research was conducted a qualitative approach, to make observations on the location of shops Kamtibmas, conducted interviews to Indramayu Police Bhabinkamtibmas personnel who perform the technical development of society in Warung Kamtibmas and to study the document to the data relating to program management Warung Kamtibmas in Indramayu. The results of this study indicate that the implementation of the stalls kamtibmas conducted through partners / co-operation with the community, perform troubleshooting and perform problem resolution activities in the community which is carried in the shop or in the police kamtibmas. Several factors are influential in the implementation of point Kamtibmas, among others, this constraint is derived minimal number of personnel, lack of socialization Bhabinkamtibmas to the public about kamtibmas stalls and the lack of means of communication. While supporting factors in the management of the shop kamtibmas, that good relations between citizens and Bhabinkamtibmas, resulting in problem solving will be quickly implemented. The results of the evaluation of the implementation of this kamtibmas stall stall kamtibmas known that the implementation of effective, visible from the indicators of success of the program which has fulfilled the function of explanation, compliance, audit and accounting function. Keywords: shop, kamtibmas, bhabinkamtibmas, disorder, society